2021
DOI: 10.12688/f1000research.28333.2
|View full text |Cite
|
Sign up to set email alerts
|

Urban educated group's perceptions of the COVID-19 pandemic management in Bangladesh: a qualitative exploration

Abstract: Background: Since the emergence of the COVID-19 outbreak, Government of Bangladesh (GoB) has taken various measures to restrict virus transmission and inform the people of the situation. However, the success of such measures largely depends on a positive public perception of the government’s ability to act decisively and the transparency of its communication. We explored public perceptions of pandemic management efforts by the Bangladeshi health sector decision-makers in this study. Methods: As this qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The country is facing di culty providing treatment facilities for all the patients. Moreover, even though the patients required hospital facilities, they have less trust in health systems for various reasons [11,12]. So, mild and moderate patients who would mostly recover without special treatment may adopt these approaches to suppress the disease from being severe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The country is facing di culty providing treatment facilities for all the patients. Moreover, even though the patients required hospital facilities, they have less trust in health systems for various reasons [11,12]. So, mild and moderate patients who would mostly recover without special treatment may adopt these approaches to suppress the disease from being severe.…”
Section: Discussionmentioning
confidence: 99%
“…There was no specialized hospital in most divisions, while 34% of the total COVID-19 dedicated general beds were in Dhaka city, and 2,542 out of 3,329 of them are occupied [8]. Therefore, despite the intention of going to hospitals, many infected individuals could not get to the hospital facilities and developed a preference for taking medications at home Studies demonstrated pervasive mistrust of the Bangladeshi people on the health systems and healthcare providers during the COVID-19 pandemic [11,12]. This distrust had made people reluctant to seek medical treatment at the hospital, and as a result, a lot of COVID-19 related deaths occurred outside hospitals; 696 people died outside hospitals, of which 662 have died at home by 22 September 2020 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The proper reconstruction of general hospitals to designated hospitals and hotels to quarantine centers were significantly crucial in preventing COVID-19 nosocomial infection. In Bangladesh, the lack of well preparation of facilities to certain hospitals during COVID-19 patients’ treatment in the early stages caused a high number of medical staffs infected with SARS-CoV-2 [ 33 ]. However, according to PCP 23, after carefully preparation, a maternity hospital was reconstructed to be a designated hospital and all medical and non-medical members didn’t get infected with SARS-CoV-2 in Wuhan.…”
Section: Methodsmentioning
confidence: 99%
“…The ongoing COVID-19 pandemic has brought multiple challenges for both healthcare providers and patients, as it has increased anxiety, distrust, and uncertainty [ 5 , 6 ], necessitating greater sensitivity to patient needs. As a result, ROP has gained attention of both policymakers and scholars from various disciplines such as public health, social psychology, social medicine, healthcare communication, and media studies.…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, various disturbing allegations have been made against the physicians by COVID-19 patients in many low- and middle-income countries, including Bangladesh, ranging from medical negligence to outright denial to provide medical services. By providing physicians with an evidence-based set of activities or behaviours during the consultation process, they would be better prepared to care for patients suffering from COVID-19, thus improving public trust in healthcare services [ 6 ].…”
Section: Introductionmentioning
confidence: 99%